Corneal Endothelial Morphology and Thickness Changes in Patients with Gout - Pınar Kösekahya; Cemile Üçgül Atılgan; Kadir Gökhan Atılgan; Mustafa Koç; Kemal Tekin; Mehtap Çağlayan; Yasin Şakir Göker (Türk Oftalmoloji Dergisi)

(untitled)
Objectives:To investigate corneal endothelial cell density (ECD), morphology, and central corneal thickness (CCT) in patients with gout compared with healthy subjects.Materials and Methods:Fifty eyes of 50 gout patients and 50 eyes of 50 healthy subjects without gout or any other systemic disease were included in this study. After detailed ophthalmologic examination, specular microscopy (Tomey EM-4000; Tomey Corp) measurement was performed for all participants. ECD, average cell area (ACA), coefficient of variation (CV), hexagonality ratio, and CCT values were recorded.Results:Mean ECD and hexagonality ratio were lower (p=0.004 and p=0.002) and CV, ACA, and CCT values were higher (p=0.001, p=0.007, and p=0.001) in patients with gout when compared to healthy subjects. There were significant correlations between gout disease duration and CD and hexagonality ratio (p=0.019 and p=0.043) and also between uric acid value and hexagonality ratio and CCT (p=0.044 and p=0.003).Conclusion:Altered corneal endothelial function was found in patients with gout when compared to healthy subjects and the alteration increased as gout duration and uric acid value increased.